A novel retroreflective planar Luneburg lens for the radar cross section enhancement. Issue 11 (2nd August 2022) - Jiao, Xin‐Hui; Wan, Guobin; Fu, Bin; Chen, Yuxu
Abstract: A novel retroreflective planar Luneburg lens for the radar cross section (RCS) enhancement is proposed in this paper. The planar Luneburg lens consists of 10 layers of metasurfaces, which are used to realize the layered permittivity distribution of three‐dimensional (3D) gradient‐index Luneburg lens. First, a single‐layer planar metasurface element is designed. The element consists of one single substrate layer and a metallic layer, and two metal square ring patches are etched on the substrate. Then, by using the transformation optics (TO) and the metasurface element, the equivalent layered permittivity distribution with 2–25 relative permittivity is realized, and elements of the planar Luneburg lens illuminated by the 30° oblique incident plane wave are designed. Finally, a 10‐layer retroreflective planar Luneburg lens at 5 GHz is designed, fabricated and measured. At 5 GHz frequency, its measured RCS values in most of the incident angle domain from −60° to 60° are enhanced in different degrees. The most notable enhancements occur in the incident angle domain around −27° and 27°, while the maximum measured RCS enhancement is more than 25 dB. This is the first time that the planar Luneburg lens is used to increase its RCSs with many incident angles.